2021
DOI: 10.1080/21655979.2021.1956403
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin receptor-mediated reactive oxygen species promotes ferroptosis of KGN cells via regulating NADPH oxidase 1/PTEN induced kinase 1/acyl-CoA synthetase long chain family member 4 signaling

Abstract: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of reproductive age. Abnormal ovarian folliculogenesis is the main factor responsible for PCOS. Iron metabolism plays a vital role in endocrine disorder. This study aimed to investigate the potentials of iron metabolism in PCOS and the underlying molecular mechanisms. Mice were injected with dehydroepiandrosterone (DHEA) to establish the PCOS model in-vivo. H & E staining was performed for histological analysis; qRT-PCR and western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 42 publications
(58 reference statements)
1
42
0
Order By: Relevance
“…TFRC mRNA overexpression influenced by ferric ammonium citrate in human osteoblast cells could decrease the osteogenesis-related mRNA expression of Runx2, alpha 1 collagen type I chain through the Hedgehog signaling pathway [ 49 ]. TFRC could induce the excessive intake of iron and then leads to excessive release of ROS through the NADPH oxidase 1 signal pathway [ 50 ]. Our bioinformatics analysis revealed that the two genes, GSTM1 and TFRC, were of significant correlation and might affect each other.…”
Section: Discussionmentioning
confidence: 99%
“…TFRC mRNA overexpression influenced by ferric ammonium citrate in human osteoblast cells could decrease the osteogenesis-related mRNA expression of Runx2, alpha 1 collagen type I chain through the Hedgehog signaling pathway [ 49 ]. TFRC could induce the excessive intake of iron and then leads to excessive release of ROS through the NADPH oxidase 1 signal pathway [ 50 ]. Our bioinformatics analysis revealed that the two genes, GSTM1 and TFRC, were of significant correlation and might affect each other.…”
Section: Discussionmentioning
confidence: 99%
“…The iron contributes to the ROS pool through the Fenton reaction [ 52 ]. Moreover, various iron-containing enzymes, such as NOXs, are involved in the process of ferroptosis [ 53 ]. In the liver, many iron ions are stored in HSCs, and iron overload may affect the development of liver fibrosis by aggravating lipid peroxidation [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“… 34 Additionally, iron‐uptake induced upregulation of ACSL4 was required for GPX4 degradation. 33 In brief, the current study suggests a key pathologic role of ACSL4 in mediating EHS‐induced skeletal muscle cell ferroptosis activation via lipid peroxidation.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, the reduction of GPX4 in presence of ASCL4 upregulation is very interesting, as suggested by previous studies demonstrating upregulation of ACSL4 induced by iron‐uptake be required for GPX4 degradation. 33 GPX4 has been proved to be an essential regulator of ferroptosis, and the insufficiency of GPX4 is thought to lead to increased levels of uncontrolled lipid peroxidation, culminating in ferroptotic cell death in vitro and in vivo . 20 , 26 However, the lipid oxidation upon GPX4 inhibition requires ACSL4, which catalyses the addition of coenzyme A to the long‐chain polyunsaturated bonds of AA or AdA, thereby promoting the esterification of polyunsaturated fatty acids to phospholipids, specifically towards the PE.…”
Section: Discussionmentioning
confidence: 99%